Intracellular traffic and polarity in brain development - Polenghi, Martina; Taverna, Elena (Frontiers in Neuroscience, 2023)
Neurons forming the human brain are generated during embryonic development by neural stem and progenitor cells via a process called neurogenesis. A crucial feature contributing to neural stem cell morphological and functional heterogeneity is cell polarity, defined as asymmetric distribution of cellular components. Cell polarity is built and maintained thanks to the interplay between polarity proteins and polarity-generating organelles, such as the endoplasmic reticulum and the Golgi apparatus. ER and GA affect the distribution of membrane components and work as a hub where glycans are added to nascent proteins and lipids. In the last decades our knowledge on the role of polarity in neural stem and progenitor cells have increased tremendously. However, the role of traffic and associated glycosylation in neural stem and progenitor cells is still relatively underexplored. In this review, we discuss the link between cell polarity, architecture, identity and intracellular traffic, and highlight how studies on neurons have shaped our knowledge and conceptual framework on traffic and polarity. We will then conclude by discussing how a group of rare diseases, called Congenital Disorders of Glycosylation (CDG) offers the unique opportunity to study the contribution of traffic and glycosylation in the context of neurodevelopment.